Level of knowledge of the body scheme in early education children (Revista Innova Educación, 2019)
The research aimed to determine the level of knowledge of the body scheme in girls and boys of the Initial Educational Institution No. 192 Puno, 2018. The methodology corresponds to the quantitative descriptive approach. The population consisted of 234 children aged 5 to 6. The data was obtained through the Goodenough Test. For the results analysis, the percentage descriptive statistic was applied. The results indicate that 30.1% of children aged 5 and 6 years have a bright level of normal knowledge. According to age, 37.5% of 6-year-olds have a much higher level of knowledge than 5-year-olds. According to sex, 23.3% girls predominate normal bright and far superior, meaning that girls have a better level of knowledge than boys. It is concluded that most children have a level of normal knowledge that is bright to far superior.
Keywords: Knowledge; body scheme; initial; girls; boys